2019
DOI: 10.3390/toxins11040209
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Aryl Hydrocarbon Receptors in the Altered Clearance of Drugs during Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is a major public health problem, since 300,000,000 people in the world display a glomerular filtration rate (GFR) below 60 mL/min/1.73m2. Patients with CKD have high rates of complications and comorbidities. Thus, they require the prescription of numerous medications, making the management of patients very complex. The prescription of numerous drugs associated with an altered renal- and non-renal clearance makes dose adjustment challenging in these patients, with frequent drug-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 166 publications
0
5
0
Order By: Relevance
“…As demonstrated by others, the binding capacity of albumin is diminished in CKD patients, most likely due to posttranslational modifications of albumin sites which could contribute to less efficient transport of uremic toxins by the renal tubular excretory machinery [ 70 , 71 , 72 ], thus resulting in further elevated plasma levels and their well-known consequences. Moreover, studies have revealed that interactions between drugs and uremic toxins could result in altered protein binding affinities [ 73 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by others, the binding capacity of albumin is diminished in CKD patients, most likely due to posttranslational modifications of albumin sites which could contribute to less efficient transport of uremic toxins by the renal tubular excretory machinery [ 70 , 71 , 72 ], thus resulting in further elevated plasma levels and their well-known consequences. Moreover, studies have revealed that interactions between drugs and uremic toxins could result in altered protein binding affinities [ 73 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is described, however, that renal failure leads to the accumulation of uremic toxins in blood and tissues. These toxins can compete with other substrates for plasma protein binding to, for example, albumin [45]. As a result, the free fraction of a substrate of albumin will be increased.…”
Section: Discussionmentioning
confidence: 99%
“…Although CKD is frequently observed in patients with cancer, many oncologic strategies interfere with kidney function. 61,102,103 CKD induces some changes in drug pharmacokinetics, 104,105 as drug absorption may increase or decrease, although it is poorly quantified. Animal and human studies indicate that drug absorption may increase because of impairment of the gut wall barrier function.…”
Section: Kidney Adverse Effects In the Tki Eramentioning
confidence: 99%